URINARY CREATINE AT REST AND AFTER REPEATED SPRINTS IN ATHLETES: A PILOT STUDY - I. Bezrati-Benayed; F. Nasrallah; M. Feki; K. Chamari; S. Omar; L. Alouane-Trabelsi; A. Ben Mansour; N. Kaabachi (Termedia Publishing House, 2014)
Creatine plays a key role in muscle function and its evaluation is important in athletes. In this study, urinary creatine concentration was measured in order to highlight its possible significance in monitoring sprinters. The study included 51 sprinters and 25 age- and sex-matched untrained subjects as a control group. Body composition was measured and dietary intake estimated. Urine samples were collected before and after standardized physical exercise. Creatine was assessed by gas chromatography mass spectrometry. Basal urinary creatine (UC) was significantly lower in sprinters than controls (34±30 vs. 74±3 μmol/mmol creatinine, p<0.05). UC was inversely correlated with body mass (r=-0.34, p<0.01) and lean mass (r=- 0.30, p<0.05), and positively correlated with fat mass (r=0.32, p<0.05). After acute exercise, urinary creatine significantly decreased in both athletes and controls. UC is low in sprinters at rest and further decreases after exercise, most likely due to a high uptake and use of creatine by muscles, as muscle mass and physical activity are supposed to be greater in athletes than untrained subjects. Further studies are needed to test the value of urinary creatine as a non-invasive marker of physical condition and as a parameter for managing Cr supplementation in athletes.